Phytochemicals as Radioprotective and Radiosensitizing Agents in Cancer Radiotherapy: Advances, Challenges, and Future Perspectives - Dweh, Tuward J.; Taye, Marylin; Deka, Dhritismita; Samanta, Suman Kumar; Talukdar, Narayan Chandra (Planta Medica)
Radiation therapy (RT) remains a fundament of cancer treatment, yet its effectiveness is often hindered by normal tissue toxicity and radiation-induced fibrosis. Recent research has highlighted the promise of bioactive-phytochemicals in enhancing the therapeutic index of RT-sensitizing tumor cells to radiation while safeguarding healthy tissues. This reflects a growing interest in integrating natural compounds with conventional cancer therapies to achieve synergistic effects. To summarize recent advances, identify the research gaps, and evaluate future directions, a comprehensive review was conducted using data from NCBI and PubChem databases, focusing on preclinical and clinical studies exploring the role of phytochemicals in cancer radiotherapy. The findings stated that, the phytochemicals such as curcumin, resveratrol, quercetin, genistein, and EGCG have been shown to sensitize cancer cells to radiation by amplifying DNA damage, promoting apoptosis, and inhibiting key signaling pathways including PI3K/Akt, ATM, and NF-κB. Simultaneously, these compounds exhibit protective effects on normal tissues by activating antioxidant responses (e.g., Nrf2/ARE), reducing oxidative stress, and alleviating radiation-induced fibrosis through modulation of CTGF and TGF-β pathways. Emerging agents like astilbin, puerarin, and isorhamnetin have also demonstrated notable radiosensitizing and antifibrotic potential. However, challenges such as poor bioavailability, dose inconsistencies, and patient-specific variability remain significant barriers to clinical translation. In conclusion, the dual context-dependent actions of phytochemicals emphasize the need for personalized therapeutic strategies, optimized dosing, and advanced delivery systems. Further, integrating nanotechnology may holds particular promise for enhancing the precision and effectiveness of phytochemical-based interventions in radiation oncology.